2007
DOI: 10.1370/afm.626
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of Treatment Options for Acute Otitis Media

Abstract: PURPOSE This study evaluated the costs and utility of observation and routine antibiotic treatment options for children with acute otitis media. METHODSThe cost-effectiveness analysis was performed among children aged 6 months to 12 years seen in primary care offi ces. The interventions studied were watchful waiting as practiced in the Netherlands, delayed prescription, 5 days of amoxicillin, and 7 to 10 days of amoxicillin. The main outcome measure was cost per quality-adjusted life-year (QALY). RESULTSIn the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 50 publications
(55 reference statements)
0
29
0
Order By: Relevance
“…At the international level, several cost analysis studies have been published concerning treatment of pharyngitis and acute otitis media, the most common infectious diseases in paediatric outpatients . A Finnish study concluded that the implementation of the guidelines on acute otitis media in children is associated with extra health benefits at slightly lower direct costs .…”
Section: Discussionmentioning
confidence: 99%
“…At the international level, several cost analysis studies have been published concerning treatment of pharyngitis and acute otitis media, the most common infectious diseases in paediatric outpatients . A Finnish study concluded that the implementation of the guidelines on acute otitis media in children is associated with extra health benefits at slightly lower direct costs .…”
Section: Discussionmentioning
confidence: 99%
“…The costs and utility of observation and routine antibiotic treatment options for children with acute OM are in the range from $132 to $157 in the United States (Coco 2007). It is a common childhood illness that is one of the most frequent reasons for medical visits and antibiotic prescriptions (Rovers 2008).…”
Section: Discussionmentioning
confidence: 99%
“…While antibiotics may benefit some children, pain relief is not immediate, the average reduction in duration of pain is only a few hours, and there is no impact on long-term hearing or ear, nose, and throat (ENT) referrals. [2][3][4][5][6][7][8][9][10] However, the NICE guidance does recommend that GPs should 'consider' immediate antibiotic treatment for two groups of children with acute otitis media -the very young (age <2 years) and those with ear discharge. The stated justification for the latter is that a posthoc meta-analysis of the clinical trial data suggests that only three children need to be treated for one less child to experience pain or fever at the 3-7-day assessment point.…”
Section: Introductionmentioning
confidence: 99%